Intensive Care in a Patient with Toxic Epidermal Necrolysis - J. Wallenborn; M. Fischer (Case Reports in Critical Care)
Toxic epidermal necrolysis (TEN) is a serious adverse drug reaction with high lethality, which usually requires intensive-medical care. A 44-year-old man developed generalized exanthema with increasing exfoliation and mucosal involvement after taking allopurinol, ibuprofen, and etoricoxib. The clinical diagnosis of TEN was histologically confirmed. Prednisolone therapy with 3 mg/kg body weight (BW) was not able to prevent further progress to finally 80% of the body surface, and infliximab 5 mg/kg BW was given as a single dose. This prevented further progression of the TEN. Despite marked improvement in skin findings, the ICU stay was prolonged by a complex analgosedation, transient kidney failure, volume management, positioning therapy, and vegetatively impeded weaning. Moreover, there was colonization with multiresistant bacteria (MRSA and VRE). Nonetheless, the patient could be restored to health and was released after four weeks. Infliximab seems to be effective in the treatment of TEN, especially in cases of rapid progression. Moreover, patients with TEN are difficult to handle in intensive-medical care, whereby attention should especially be paid to sufficient pain therapy, and the positioning of the patient is a particular challenge.